AYAT-AYAT TENTANG RELASI LAKI-LAKI DAN PEREMPUAN DALAM AL-QUR’AN: Analisis Struktural Levi-Strauss - Faizah, Nur (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
Religion is a social institution, especially for the Muslim community in general, determine the dynamics of the entire development community. In many cases the social processes that marginalizing women, intentionally or not, often involving religion as elements forming knowledge about relationships between men and women are unequal, and often used as a source of theological legitimacy of the above indisputable fact that marginalize women. During this time, the field of study of the Qur’an many scholars dominated philology and history. This led to a prolonged confusion between the text and the history of salvation history, which is implicit in it. This needs to be solved, with the view that the text of the Qur'an and his commentary as an expression of the views of Islam. This is where the importance of the legacy of structuralism in a given interpretation. By using Levi-Strauss' structuralism, an attempt to determine the relationship webs in the narrative, the relationship is either syntagmatic or paradigmatic, to find hidden messages or messages that are deepest in the verses of the Qur’an. [Agama merupakan institusi sosial, terutama untuk masyarakat muslim pada umumnya, sangat menentukan seluruh perkembangan dinamika masyarakat. Dalam banyak kasus proses sosial yang memarginalisasikan perempuan, sengaja atau tidak, sering melibatkan agama sebagai unsur pembentuk pengetahuan tentang relasi laki-laki-perempuan yang timpang dan seringkali dijadikan sumber legitimasi teologis yang tidak terbantahkan atas kenyataan yang menyudutkan perempuan. Selama ini, bidang kajian al-Qur’an banyak didominasi sarjana filologi dan sejarah. Ini memunculkan kerancuan berkepanjangan antara sejarah teks tersebut dan sejarah penyelamatan, yang secara implisit terkandung di dalamnya. Hal ini perlu dipecahkan, dengan memandang bahwa teks al-Qur’an dan tafsirnya sebagai ungkapan pandangan-pandangan Islam. Di sinilah pentingnya strukturalisme dalam memberi kekayaan khazanah penafsiran. Dengan menggunakan strukturalisme Levi-Strauss, sebuah upaya untuk mengetahui jaring-jaring relasi dalam narasi, baik relasi tersebut bersifat sintagmatik maupun paradigmatik, untuk mengetahui hidden message atau pesan terdalam yang terdapat dalam ayat-ayat al-Qur’an.]